The Application of a Graded Approach in the Management System Requirements to Radiation Protection for Nuclear Facility (Journal of Nuclear Technology in Applied Science, 2025)
A graded approach meets the requirements for all phases of a nuclear facility’s lifespan, including site selection, evaluation, design, construction, commissioning, operation, and decommissioning. The application of management system requirements should be assessed for each process, system, product item, component, structure, activity, service, or control. The International Atomic Energy Agency (IAEA) incorporates the principle of a graded approach as a fundamental element to ensure safety at nuclear facilities.This study utilizes a graded approach to implement management system requirements for radiation protection. It identifies key aspects that must be considered during grading. Management system requirements are largely relevant to the regulation of the working environment, human resource management, strategic planning, and performance monitoring and evaluation.The paper illustrates the implementation of an organized methodology for applying radiation protection requirements. It presents practical examples such as the categorization of work areas and the subsequent classification of zones within each area, control of access to these areas, establishment of local regulations, supervision of work activities, monitoring of workplaces and individuals, planning and authorization of work permits, and provision of appropriate protective clothing and equipment.The importance of applying the graded approach to enhance facility safety is emphasized through common practical examples. The study highlights the necessity of familiarizing staff with the characteristics of the facility or activity in order to prepare reference documents for operational procedures according to safety significance and complexity. Consideration is given to potential impacts on human life, health, and the environment, required corrective actions for possible consequences of unanticipated events or improperly performed activities, levels of control in relation to available resources, and associated risks.Moreover, a case study addressing both external and internal radiation doses received by facility staff is presented as a practical example of optimization using the graded approach.
Keywords: Nuclear Facility; Graded Approach; Radiation Protection; Management System; Regulations